A Dual-Band Reconfigurable Antenna for IoT Devices in Congested Spectrum Environments - Bostani, Ali (2025)
Spectral congestion has become critical in modern wireless environments because of the enormous growth of Internet of Things (IoT) devices. Therefore, a compact dual-band reconfigurable antenna capable of real-time frequency agility is designed and implemented using PIN diode–based switching to alleviate these challenges. The antenna is fabricated on a low-cost FR4 substrate that is amenable to mass deployment of the antenna in the scale of mass market IoT systems. A dual-band engineering proposal for this antenna is made to be efficient in two IoT communication bands widely used today: 2.4 GHz and 5.2 GHz. CST Microwave Studio was used to perform full-wave electromagnetic simulations that were then experimentally validated by VNA. Stable directional radiation patterns are observed through the bands, a measured return loss better than ?18 dB, which confirms robust impedance matching, and a peak gain of 4.2 dBi. In addition, the reconfiguration time of the PIN diode switching mechanism is less than 10 µs, resulting in near-instanta-neous reconfiguration to changing spectrum conditions. These performance characteristics attest to the antenna’s viability in time-sensitive, interference-aware IoT applications such as smart homes, industrial automation, and wearables. The results show how the combi-nation of agile antenna architecture helps improve spectral efficiency, robustness of the links, and communication robustness in the future wireless networks.